Factors Influencing Auditors' Going Concern Opinion - Haron, Hasnah; Hartadi, Bambang; Ansari , Mahfooz; Ismail, Ishak (Asian Academy of Management (AAM), 2009)
The main purpose of our study is to provide evidence the practically consideration of auditor judgement on going concern opinion. By using quasi experimental, we found strong evidence that auditors' judgement is affected by financial indicators, evidence, and disclosure. We have another finding that consensus among auditors' judgement and the interaction effects between the three independent variables is significant.